2005
DOI: 10.1007/s11101-005-4053-9
|View full text |Cite
|
Sign up to set email alerts
|

Saponins in Calendula officinalis L. – Structure, Biosynthesis, Transport and Biological Activity

Abstract: Trends in research on Calendula officinalis L. saponins performed in Department of Plant Biochemistry at Warsaw University are reviewed. Calendula officinalis, a well known medicinal plant, contains significant amounts of oleanane saponins, which form two distinct series of related compounds, called ''glucosides'' and ''glucuronides'' according to the structure of the respective precursor. Both series differ in the pathway of their biosynthesis and further metabolism, i.e. the rate of formation and stages of p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
47
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(51 citation statements)
references
References 28 publications
1
47
2
1
Order By: Relevance
“…The anticancer, antibacterial, fungicidal, and antioxidant activities of C. officinalis L have been frequently attributed to saponins and carotenoids produced by the plant [3,20,22]. Our results suggest that treatment of the marigold plant with SNPs and MeJA can be a good strategy for increasing its medicinal properties.…”
Section: Discussionmentioning
confidence: 70%
See 3 more Smart Citations
“…The anticancer, antibacterial, fungicidal, and antioxidant activities of C. officinalis L have been frequently attributed to saponins and carotenoids produced by the plant [3,20,22]. Our results suggest that treatment of the marigold plant with SNPs and MeJA can be a good strategy for increasing its medicinal properties.…”
Section: Discussionmentioning
confidence: 70%
“…The elicitor function of SNPs through increased ROS formation and membrane lipid peroxidation has also been reported in certain fresh water microalgae [15]. Previous studies have also shown that C. officinalis L extract can effectively scavenge DPPH stable free radicals, superoxide, and hydroxyl radicals, as well as inhibit tissue lipid peroxidation in vitro, in a concentrationdependent manner [1,3]. However, our data demonstrates that this capacity decreased after treatment with different concentrations of SNP and MeJA, which was consistent with other reports [14].…”
Section: Discussionmentioning
confidence: 80%
See 2 more Smart Citations
“…In plants, specifically, they exist in the epicuticular waxes as a first defense barrier against pathogens (Heinzen et al 1996) and may function as defense compounds against pathogens or as allelopathic agents (Szakiel et al 2005). This suggests a potentially crucial role for these components as key biomolecular components to be added to future vaccines against high methanogenesis in the rumen, possibly through their antibacterial (Pollier and Goossens 2012) or anti-proliferative (Neto 2007) activity.…”
Section: Resultsmentioning
confidence: 99%